Neuromagnetic high-frequency oscillations correlate with seizure severity in absence epilepsy. Issue 2 (February 2016) - Tang, Lu; Xiang, Jing; Huang, Shuyang; Miao, Ailiang; Ge, Huaiting; Liu, Hongxing; Wu, Di; Guan, Qingshan; Wu, Ting; Chen, Qiqi; Yang, Lu; Lu, Xiaopeng; et al.
Highlights: Neuromagnetic changes from interictal to ictal periods predominantly occurred in medial prefrontal cortex and parieto-occipito-temporal junction in absence seizures. Significant differences between interictal and ictal activities were found in low-frequency bands (<30 Hz). The strength of ictal high-frequency oscillations (200–1000 Hz) significantly correlated with the severity of absence seizures. Abstract: Objective: This study quantified the clinical correlation of interictal and ictal neuromagnetic activities from low- to very-high-frequency ranges in childhood absence epilepsy (CAE). Methods: Twelve patients with clinically diagnosed drug-naïve CAE were studied using a 275-channel whole-head magnetoencephalography (MEG) system. MEG data were digitized at 6000 Hz and analyzed at both sensor and source levels with multi-frequency analyses. Results: Neuromagnetic changes from interictal to ictal periods predominantly occurred in medial prefrontal cortex and parieto-occipito-temporal junction in absence seizures. The changes were statistically significant in low-frequency bands only (<30 Hz, p  < 0.0001). There was a significant correlation between the source strength of ictal high-frequency oscillations (HFOs) in 200–1000 Hz and the number of daily seizures ( r  = 0.734, p  < 0.01). Conclusions: CAE has focal neuromagnetic sources. The transition from interictal to ictal periods is associated with the elevation of low-frequency brain activities. The strength of HFOs reflects the severity of absence seizures. Significance: Low- and high-frequency MEG signals reveal distinct brain activities in CAE. HFOs is a new biomarker for the study of absence seizures.